2006
DOI: 10.1590/s1676-06032006000200023
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento de Mollusca, Crustacea e Echinodermata associados a Sargassum spp. na Ilha da Queimada Pequena, Estação Ecológica dos Tupiniquins, litoral sul do Estado de São Paulo, Brasil

Abstract: This work represents the first effort to assess the phytal macrofauna of Queimada Pequena island and was focused in mollusks, crustaceans and echinoderms associated to Sargassum spp. Sampling of the macrofauna was performed by random collections of 6 Sargassum fronds 6 m deep using SCUBA. The fronds were sealed underwater in individual 200 μm mesh bags and detached from the rocky shore. The samples were preserved in recipients in 10% formalin and carried to the laboratory to remove and identify the associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 19 publications
1
13
2
7
Order By: Relevance
“…Similar records had already been found for phytal assemblages of other algae species and from other localities (Montouchet 1979, Schézy & Paula 2000, Chemello & Milazzo 2002, Jacobucci & Leite 2002, Jacobucci et al 2006, Almeida 2007, Leite et al 2009, Veras 2011. Many families identified in this work, including the most abundant ones (Cerithiidae, Phasianellidae and Columbellidae) have recurrent records in general phytal studies already developed in Brazil (Montouchet 1979, Jacobucci et al 2006, Almeida 2007, Leite et al 2009, Veras 2011.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Similar records had already been found for phytal assemblages of other algae species and from other localities (Montouchet 1979, Schézy & Paula 2000, Chemello & Milazzo 2002, Jacobucci & Leite 2002, Jacobucci et al 2006, Almeida 2007, Leite et al 2009, Veras 2011. Many families identified in this work, including the most abundant ones (Cerithiidae, Phasianellidae and Columbellidae) have recurrent records in general phytal studies already developed in Brazil (Montouchet 1979, Jacobucci et al 2006, Almeida 2007, Leite et al 2009, Veras 2011.…”
Section: Discussionsupporting
confidence: 79%
“…predation, competition, recruitment and migration) and abiotic factors (e.g. hydrodynamism, nutrients availability, habitat structure, light incidence and temperature) (Chemello & Milazzo 2002, Jacobucci & Leite 2002, Leite et al 2009). In these communities, algae provide several advantages for invertebrate and vertebrate animals inhabiting their fronds, including protection against desiccation, wave action and predators, better temperature and salinity conditions, as well as food resources (Jacobucci & Leite 2002, Jacobucci et al 2006, Leite et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The physicochemical properties of water strongly influence coastal communities in different marine systems (JACOBUCCI et al, 2006). In this study, the sites sampled showed no great differences in water temperature and dissolved oxygen.…”
Section: Discussionmentioning
confidence: 58%